PENINGKATAN HASIL BELAJAR GEJALA KEMAGNETAN MELALUI INKUIRI TERBIMBING BERBANTUAN KANTONG MISTERI MAGNETIK - Natasya Tamau; Abdul Haris Panai; Gamar Abdullah; Kudus; Rifda Mardian Arif (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2026)
This study aims to improve the learning outcomes of third-grade students at SDN 8 Telaga on magnetic phenomena material by implementing the Mysterious Magnetic Bag media and a guided inquiry model. This Classroom Action Research (CAR) was conducted in two cycles, comprising planning, acting, observing, and reflecting stages. Data collection utilized observation, tests, and documentation involving 20 student subjects. Initial observations revealed that only 4 out of 15 present students (26.67%) achieved learning mastery with a minimum passing score of . Following the intervention in Cycle I, the mastery level increased to 66.67%, representing 10 out of 15 students. Strategic improvements in Cycle II resulted in a significant surge in mastery reaching 100%, where all 19 present students scored above the minimum passing threshold. This achievement exceeded the established success indicator of 75%. This demonstrates that integrating concrete manipulative media within a guided inquiry framework effectively constructs tangible scientific understanding, making it highly recommended as a pedagogical instrument to overcome conventional learning passivity